If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -12 = 14 Reorder the terms: -12 + 4y = 14 Solving -12 + 4y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4y = 14 + 12 Combine like terms: -12 + 12 = 0 0 + 4y = 14 + 12 4y = 14 + 12 Combine like terms: 14 + 12 = 26 4y = 26 Divide each side by '4'. y = 6.5 Simplifying y = 6.5
| 2y-7x=-10 | | 3x+2[x+7]-5=4[x+3]-3[x+1] | | 20x-15=-8 | | 8w^2-18+9= | | 6H+H-20=44-H | | 2[4+2(5-x)-2x]=4(7-2x) | | 6H+H-20=44 | | 2z^2=5z-2 | | 2x+9x+12=6 | | 2x^2-4y=8 | | y-7=3(x-6) | | 8x-28=16+6x | | 70x+25(80)=60x+60(80) | | 4(1+X)=2(2+X) | | 14=50x | | x+7=-61 | | -2x-8=-13x-4 | | -5=25x | | -16x=224 | | 111n-9=5n+27 | | 15*15x=144 | | (2x+3)x(3x-6)= | | 1.5(2a+1)=5(0.5a+0.3)+0.1 | | (0.8g+0.6-0.3)=(0.1-0.2h+0.8g) | | -x-5=3x+19 | | x^2+4*x-7=2*x-4 | | 2x-20=2x+10 | | 5x+(-2)=20 | | (5x-9)(2x+4)= | | -22=-7+3y | | -59+3x=2x+21 | | 5(0)+y=20 |